The impact of ownership structure and corporate governance on executive compensation: Empirical evidence from Chinese listed companies - LUO, Shichen (2020)
Executive compensation and its correlation with corporate governance is a broad topic in academics. The objective of this dissertation is to study executive compensation and its determinants in Chinese practices. This dissertation uses quantitative analysis method and conducts empirical analysis through STATA statistical software. This study use data from 3,456 listed companies from Shanghai and Shenzhen Stock Exchange from 2016 to 2018, to study the relationship between executive compensation and corporate governance. Besides, due to the specific Chinese ownership characteristics, this study also examines the impact of ownership structure on executive compensation. Corporate governance practice in China imitate many of the key features of the Anglo-Saxon economies, and most of the findings in this study are in line with the results of prior researches examining the same relationship between executive compensation and several determinants. Overall, this study provides a very important practical significance for deepening market reform, improving the compensation incentive system, and then improving the corporate governance mechanism in China. More importantly, since the existing literature mainly studies the Anglo-Saxon countries, by studying Chinese practice, this study fills up the gap of the non-Anglo-Saxon governance system in the international literature and provides some guidance for other transition economies fit.